Triazine / heptazine homojunction structure carbon-doped carbon nitride photocatalyst as well as preparation method and application thereof
By adopting the preparation method of a triazine/heptaazine homojunction structure carbon doped carbon nitride photocatalyst, the existing photocatalysts have been solved, and the problems of low efficiency and high by-product generation in catalytic benzyl alcohol oxidation reaction are achieved, Environmentally friendly aromatic aldehyde preparation.
Patent Information
- Application Number
- CN202411422879.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The existing photocatalysts have problems such as low efficiency, numerous by-product generation, and harsh process conditions in catalytic benzyl alcohol oxidation reaction, making it difficult to achieve green and efficient preparation of aromatic aldehydes.
The preparation method of a carbon-doped carbon nitride photocatalyst is adopted for the preparation of a triazine/heptanazine homojunction structure carbon doped carbon nitride photocatalyst by calcining a mixture of melamine and 2,4,6-triaminopyrimidine to form a carbon-doped triazine/heptanazine precursor. And calcined in the molten salt to prepare a carbon nitride photocatalyst with a uniform homogeneous junction interface.
Catalyst preparation without organic solvent is achieved, the stability and photocatalytic activity of the catalyst are improved, the light absorption range is expanded, the selective oxidation efficiency of benzaldehyde is improved, and the process is environmentally friendly and cost-effective.
Smart Images

Figure CN119500212A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalysts, and in particular relates to a preparation method of a triazine / heptazine homojunction structure carbon-doped carbon nitride photocatalyst, a product thereof and an application thereof. Background Art
[0002] Aromatic aldehydes are important chemical intermediates and are widely used in pesticides, medicines, dyes, food and other industries. For example, benzaldehyde is mostly prepared from toluene as a raw material in industrial production, which is obtained by side chain chlorination, toluene hydrolysis or toluene oxidation. The reaction conditions are relatively harsh, and the yield and selectivity are not ideal. The large amount of acid and alkali consumed can easily cause secondary pollution, which is not conducive to green and sustainable development. Therefore, finding a green and efficient route for the preparation of aromatic aldehyde products is of great significance to the development of modern green chemical industry.
[0003] The green synthesis technology of preparing aromatic aldehydes by oxidation of benzyl alcohol has attracted widespread attention. Compared with traditional industrial methods, it has the advantages of simple process, environmental friendliness and low cost. At present, a variety of catalysts for the liquid phase oxidation of benzyl alcohol to prepare benzaldehyde have been developed, mainly supported noble metal catalysts (such as Ru, Pd, Pt-based catalysts, etc.) and non-noble metal catalysts (such as Mn, Fe, Co-based catalysts, etc.), but they still need to be carried out at high temperature and high pressure in organic solvents, and by-products are often generated to affect efficiency. Therefore, it is crucial to find a greener and more sustainable catalytic system.
[0004] Artificial photosynthesis technology can directly use solar energy to oxidize benzyl alcohol. Under mild conditions, the conversion of target aldehydes or acid products can be achieved by controlling the reaction system. It is an effective method for the green synthesis of aromatic aldehydes. The core of this technology lies in the design and development of semiconductor photocatalysts with excellent performance. Compared with traditional metal-based semiconductor photocatalysts (such as TiO 2 、CdS、Ni 2 P, InN, etc.), graphite carbon nitride (gC 3 N 4 ) as a non-metallic semiconductor photocatalyst, has the advantages of simple preparation process and stable physical and chemical properties. Due to its unique network structure and visible light response, as well as its excellent adsorption and activation ability for aromatic compounds, it has become a widely studied catalytic photocatalyst in the field of photocatalytic selective oxidation of benzyl alcohol. However, the traditional bulk carbon nitride (Bulk gC nitride) prepared by direct thermal polymerization using nitrogen-containing small molecules (such as melamine, urea, dicyandiamide, etc.) as precursors is still not widely used. 3 N 4 ) usually has problems such as small specific surface area, low visible light utilization, and serious photogenerated electron-hole recombination. Currently, the photocatalytic oxidation of benzyl alcohol cannot achieve the expected effect.
[0005] Carbon nitride is compounded with other semiconductors to construct a heterojunction. The heterojunction between the two materials and the existence of a built-in electric field are conducive to promoting the separation and migration of photogenerated carriers and improving the photon quantum efficiency. However, heterojunctions are usually combined by electrostatic attraction or van der Waals interaction, and their strength is usually weak, resulting in poor stability of catalytic material performance. In contrast, homojunctions are obtained by coupling different phases of the same material, and the physical and chemical properties of each phase material are similar. By constructing a homojunction at the molecular level, it is possible to ensure close contact between the two phases and improve the stability of the material. At the same time, the combination of physically and chemically similar phases can effectively eliminate unnecessary interface defects and provide an unobstructed channel for photogenerated carriers. For graphite phase carbon nitride, the currently reported homojunction construction method mainly mixes triazine and heptazine-based precursors on the surface, and the heptazine monomers such as melem and the triazine-heptazine mixtures obtained at different temperatures are compact and difficult to disperse. The carbon nitride prepared under molten salt has a homojunction interface only at the contact interface between the two phases, which is not evenly distributed, and has limited performance improvement. Summary of the invention
[0006] The purpose of the present invention is to address the above shortcomings and provide a method for preparing a triazine / heptazine homojunction structure carbon-doped carbon nitride photocatalyst and its products and applications.
[0007] On the one hand, the present invention provides a method for preparing a triazine / heptazine homojunction structure carbon-doped carbon nitride photocatalyst, the specific steps are:
[0008] (1) A mixed powder of melamine and 2,4,6-triaminopyrimidine is placed in air, heated to 300° C. to 500° C., and calcined for 2 to 6 hours to form a mixture of carbon-doped melamine and its oligomers.
[0009] This step can adjust the ratio of triazine to heptazine in the mixture of carbon-doped melamine and its oligomers by changing the calcination temperature;
[0010] (2) placing the mixture obtained in step (1) in water at 60 to 70° C., dispersing by ultrasonication, then slowly cooling to room temperature and oscillating for 12 to 36 hours, removing water by rotary evaporation, and further drying to obtain a solid supramolecular precursor;
[0011] This step uses supramolecular self-assembly to rearrange the precursor molecules, making them more fluffy on a macroscopic level so that they can be mixed more evenly with the molten salt; on a microscopic level, the triazine and heptazine components are evenly mixed, which is more conducive to obtaining a uniform triazine / heptazine homojunction structure.
[0012] (3) After the solid supramolecular precursor obtained in step (2) is fully mixed with the molten salt, it is calcined at 500° C. to 600° C. for 2 to 6 hours, cooled and fully washed with deionized water to remove the mixed salt, separate the solid residue, and dry to obtain a triazine / heptazine homojunction structure carbon-doped carbon nitride photocatalyst THCN. x -t, (wherein x is the amount of 2,4,6-triaminopyrimidine added based on 10 g of melamine; t is the preparation temperature of the carbon-doped triazine / heptazine mixture precursor).
[0013] This step adopts calcination in molten salt to prepare carbon nitride containing triazine / heptazine homojunction structure. The molten salt reaction environment can maintain the triazine and heptazine units of the raw material, so that the prepared carbon nitride contains triazine and heptazine structures.
[0014] By the method provided by the present invention, a homojunction structure is formed, which is obtained by coupling different phases of the same material, and each phase material has similar physical and chemical properties. By constructing a homojunction from a molecular level, it is possible to ensure that the two phases are in close contact, improve material stability, and at the same time, the phases with similar physical and chemical properties can effectively eliminate unnecessary interface defects and provide barrier-free channels for photogenerated carriers. Graphite phase carbon nitride has exactly two configurations, namely triazine-based carbon nitride with triazine ring as a repeating unit, and heptazine-based carbon nitride with heptazine ring as a repeating unit, and the carbon nitride of the two configurations has a natural advantage in homogeneous structure construction, and the homogeneous structure construction method reported at present mainly mixes triazine and heptazine-based precursors in appearance, and heptazine monomers such as melem and triazine-heptazine mixture blocks obtained at different temperatures are compact, difficult to disperse, and the carbon nitride prepared under molten salt, its homojunction interface is only present at the two-phase contact interface, not uniformly distributed, and limited to performance improvement. In contrast, there are few reports on the construction of carbon nitride photocatalysts with homojunction structures at the molecular level. In addition, the carbon doping of the carbon nitride skeleton in the present invention can destroy the planar symmetrical triazine or tris-triazine skeleton structure, stimulate π-π* electron transitions, and broaden the light absorption range of the photocatalyst. At the same time, the doped carbon can also serve as a capture center for photogenerated electrons or holes, improve the separation efficiency of photogenerated carriers, and further improve the photocatalytic activity of the photocatalyst.
[0015] Furthermore, in step (1), the heating rate is 5°C·min -1 .
[0016] Furthermore, in the step (1), the mass ratio of melamine to 2,4,6-triaminopyrimidine is 10:0.02-0.5.
[0017] Furthermore, in the step (1), the mass ratio of melamine to 2,4,6-triaminopyrimidine is 10:0.05.
[0018] Furthermore, in step (2), the mixture is ground into fine powder before being ultrasonically dispersed in water, and the concentration of the mixture in water is 25 g / L.
[0019] Furthermore, in the step (3), the molten salt is a composition of KCl and LiBr, and the mass ratio of the solid supramolecular precursor, KCl and LiBr is 1:2.75:2.25.
[0020] The second aspect of the present invention also provides a triazine / heptazine homojunction structure carbon-doped carbon nitride photocatalyst prepared by the above preparation method.
[0021] The third aspect of the present invention also provides an application of the above triazine / heptazine homojunction structure carbon-doped carbon nitride photocatalyst in photocatalytic selective oxidation.
[0022] Furthermore, the application is to use benzyl alcohol as a reaction substrate, acetonitrile as a reaction medium, carbon-doped carbon nitride as a photocatalyst, a xenon lamp as a light source, add an oxidant, form a reaction system, and prepare benzaldehyde and / or benzoic acid.
[0023] Furthermore, the reaction conditions are as follows: the reaction temperature is controlled at 60°C, the reaction time is 1 to 12 hours, and the concentration of benzyl alcohol in the reaction system is 50 mmol·L -1 , the carbon nitride photocatalyst concentration is 4 g·L -1 , the oxidant is oxygen.
[0024] Beneficial effects of the present invention:
[0025] (1) The triazine / heptazine homojunction carbon-doped carbon nitride photocatalyst does not use any organic solvents during the preparation process. Only water is used as the solvent, which is safe, environmentally friendly and simple to prepare.
[0026] (2) The ratio of triazine molecules to heptazine molecules in the precursor can be adjusted by controlling the preparation temperature of the mixture. This method is simple and effective.
[0027] (3) Prepolymerization of 2,4,6-triaminopyrimidine and melamine to form a carbon-doped triazine / heptazine precursor for the preparation of carbon nitride can effectively prevent the rapid sublimation of 2,4,6-triaminopyrimidine and improve the structural integrity of the carbon nitride skeleton to facilitate the rapid transmission of photogenerated carriers.
[0028] (4) The molten salt method is conducive to the directional regulation of the repeating units of carbon nitride photocatalysts. Using a mixture of triazine and heptazine as a precursor, a carbon nitride catalyst with a triazine / heptazine homojunction structure can be obtained.
[0029] (5) The operation of first crushing the precursor and then self-assembling it in water can promote the rearrangement of triazine and heptazine molecules and improve their dispersibility in molten salt, which is conducive to obtaining a carbon nitride photocatalyst with uniform distribution at the triazine / heptazine homojunction interface. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 THCN prepared in Example 3 0.05 -SEM image of 400 photocatalyst;
[0031] Figure 2 XRD patterns of the photocatalysts prepared in Examples 1 to 6 and Comparative Example 1;
[0032] Figure 3 UV-visible diffuse reflectance spectra of the photocatalysts prepared in Example 3 and Comparative Example 1;
[0033] Figure 4 Tauc plots of the photocatalysts prepared in Example 3 and Comparative Example 1;
[0034] Figure 5 THCN prepared in Example 3 0.05 -400 photocatalyst photocatalytic benzyl alcohol oxidation cycle performance diagram (each cycle 4h);
[0035] Figure 6 THCN prepared in Example 3 0.05 -400 photocatalyst photocatalytic benzyl alcohol oxidation cycle performance diagram (each cycle is 12h). DETAILED DESCRIPTION
[0036] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the examples in the specification. The methods described are all conventional methods unless otherwise specified, and the original photocatalysts can be obtained from public commercial channels unless otherwise specified.
[0037] The term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0038] The preparation method of the triazine / heptazine homojunction structure carbon-doped carbon nitride photocatalyst provided by the present invention comprises the following specific steps:
[0039] (1) placing a mixed powder of melamine and 2,4,6-triaminopyrimidine in air, heating it to 300° C. to 500° C., and calcining it for 2 to 6 hours to form a mixture of carbon-doped melamine and its oligomers;
[0040] (2) placing the mixture obtained in step (1) in water at 60 to 70° C., dispersing by ultrasonication, then slowly cooling to room temperature and oscillating for 12 to 36 hours, removing water by rotary evaporation, and further drying to obtain a solid supramolecular precursor;
[0041] (3) After the solid supramolecular precursor obtained in step (2) is fully mixed with the molten salt, it is calcined at 500° C. to 600° C. for 2 to 6 hours, cooled and fully washed with deionized water to remove the mixed salt, separate the solid residue, and dry to obtain a triazine / heptazine homojunction structure carbon-doped carbon nitride photocatalyst THCN. x -t.
[0042] The following is a detailed description of the raw material feeding amount and the specific reaction conditions in the examples.
[0043] Triazine / heptazine homojunction carbon-doped carbon nitride photocatalyst labeled as THCN x -t, wherein x is the amount of 2,4,6-triaminopyrimidine added based on 10 g of melamine; and t is the preparation temperature of the carbon-doped triazine / heptazine mixture precursor.
[0044] Example 1
[0045] THCN 0.05 Preparation of -300 photocatalyst:
[0046] (1) 10 g of melamine and 0.05 g of 2,4,6-triaminopyrimidine powder were placed in a mortar and mixed thoroughly. The mixture was then transferred to a crucible and calcined at 300 °C for 4 h (the heating rate was 5 °C min -1 ) to obtain a carbon-doped triazine / heptazine mixture.
[0047] (2) The mixture obtained in step (1) was ultrasonically dispersed in water at 60° C., then slowly cooled to room temperature and shaken for 24 h, the water was removed by rotary evaporation (the heating temperature was controlled at 60° C.), and then placed in a vacuum oven at 40° C. for further drying to obtain a solid supramolecular precursor.
[0048] (3) The supramolecular precursor (1 g) obtained in step (2) was uniformly mixed with KCl (2.75 g) and LiBr (2.25 g) and then transferred to a covered crucible and calcined at 550 °C for 4 h (heating rate of 5 °C min-1) in air atmosphere. -1 ), after natural cooling, the mixture was fully washed with deionized water to remove the mixed salt, the solid residue was separated, and the homogeneous carbon-doped carbon nitride photocatalyst THCN was obtained by drying. 0.05 -300.
[0049] Example 2
[0050] THCN 0.05 -350 Photocatalyst preparation:
[0051] (1) 10 g of melamine and 0.05 g of 2,4,6-triaminopyrimidine powder were placed in a mortar and mixed thoroughly. The mixture was then transferred to a crucible and calcined at 350 °C for 4 h (heating rate was 5 °C min -1 ) to obtain a carbon-doped triazine / heptazine mixture.
[0052] (2) The mixture obtained in step (1) was ultrasonically dispersed in water at 60° C., then slowly cooled to room temperature and shaken for 24 h, the water was removed by rotary evaporation (the heating temperature was controlled at 60° C.), and then placed in a vacuum oven at 40° C. for further drying to obtain a solid supramolecular precursor.
[0053] (3) The supramolecular precursor (1 g) obtained in step (2) was uniformly mixed with KCl (2.75 g) and LiBr (2.25 g) and then transferred to a covered crucible and calcined at 550 °C for 4 h (heating rate of 5 °C min-1) in air atmosphere. -1 ), after natural cooling, the mixture was fully washed with deionized water to remove the mixed salt, the solid residue was separated, and the homogeneous carbon-doped carbon nitride photocatalyst THCN was obtained by drying. 0.05 -350.
[0054] Example 3
[0055] THCN 0.05 -400 Photocatalyst preparation:
[0056] (1) 10 g of melamine and 0.05 g of 2,4,6-triaminopyrimidine powder were placed in a mortar and mixed thoroughly. The mixture was then transferred to a crucible and calcined at 400 °C for 4 h (heating rate was 5 °C min -1 ) to obtain a carbon-doped triazine / heptazine mixture.
[0057] (2) The mixture obtained in step (1) was ultrasonically dispersed in water at 60° C., then slowly cooled to room temperature and shaken for 24 h, the water was removed by rotary evaporation (the heating temperature was controlled at 60° C.), and then placed in a vacuum oven at 40° C. for further drying to obtain a solid supramolecular precursor.
[0058] (3) The supramolecular precursor (1 g) obtained in step (2) was uniformly mixed with KCl (2.75 g) and LiBr (2.25 g) and then transferred to a covered crucible and calcined at 550 °C for 4 h (heating rate of 5 °C min-1) in air atmosphere. -1), after natural cooling, the mixture was fully washed with deionized water to remove the mixed salt, the solid residue was separated, and the homogeneous carbon-doped carbon nitride photocatalyst THCN was obtained by drying. 0.05 -400.
[0059] Figure 1 THCN prepared in Example 3 0.05 -400 catalyst SEM image, the catalyst exhibits an amorphous structure and a loose and porous surface.
[0060] Example 4
[0061] THCN 0.05 -425 Preparation of photocatalyst:
[0062] (1) 10 g of melamine and 0.05 g of 2,4,6-triaminopyrimidine powder were placed in a mortar and mixed thoroughly. The mixture was then transferred to a crucible and calcined at 425 °C for 4 h (heating rate was 5 °C min -1 ) to obtain a carbon-doped triazine / heptazine mixture.
[0063] (2) The mixture obtained in step (1) was ultrasonically dispersed in water at 60° C., then slowly cooled to room temperature and shaken for 24 h, the water was removed by rotary evaporation (the heating temperature was controlled at 60° C.), and then placed in a vacuum oven at 40° C. for further drying to obtain a solid supramolecular precursor.
[0064] (3) The supramolecular precursor (1 g) obtained in step (2) was uniformly mixed with KCl (2.75 g) and LiBr (2.25 g) and then transferred to a covered crucible and calcined at 550 °C for 4 h (heating rate of 5 °C min-1) in air atmosphere. -1 ), after natural cooling, the mixture was fully washed with deionized water to remove the mixed salt, the solid residue was separated, and the homogeneous carbon-doped carbon nitride photocatalyst THCN was obtained by drying. 0.05 -425.
[0065] Example 5
[0066] THCN 0.05 -450 Photocatalyst preparation:
[0067] (1) 10 g of melamine and 0.05 g of 2,4,6-triaminopyrimidine powder were placed in a mortar and mixed thoroughly. The mixture was then transferred to a crucible and calcined at 450 °C for 4 h (heating rate was 5 °C min -1 ) to obtain a carbon-doped triazine / heptazine mixture.
[0068] (2) The mixture obtained in step (1) was ultrasonically dispersed in water at 60° C., then slowly cooled to room temperature and shaken for 24 h, the water was removed by rotary evaporation (the heating temperature was controlled at 60° C.), and then placed in a vacuum oven at 40° C. for further drying to obtain a solid supramolecular precursor.
[0069] (3) The supramolecular precursor (1 g) obtained in step (2) was uniformly mixed with KCl (2.75 g) and LiBr (2.25 g) and then transferred to a covered crucible and calcined at 550 °C for 4 h (heating rate of 5 °C min-1) in air atmosphere. -1 ), after natural cooling, the mixture was fully washed with deionized water to remove the mixed salt, the solid residue was separated, and the homogeneous carbon-doped carbon nitride photocatalyst THCN was obtained by drying. 0.05 -450.
[0070] Example 6
[0071] THCN 0.05 -500 Photocatalyst preparation:
[0072] (1) 10 g of melamine and 0.05 g of 2,4,6-triaminopyrimidine powder were placed in a mortar and mixed thoroughly. The mixture was then transferred to a crucible and calcined at 500 °C for 4 h (the heating rate was 5 °C min -1 ) to obtain a carbon-doped triazine / heptazine mixture.
[0073] (2) The mixture obtained in step (1) was ultrasonically dispersed in water at 60° C., then slowly cooled to room temperature and shaken for 24 h, the water was removed by rotary evaporation (the heating temperature was controlled at 60° C.), and then placed in a vacuum oven at 40° C. for further drying to obtain a solid supramolecular precursor.
[0074] (3) The supramolecular precursor (1 g) obtained in step (2) was uniformly mixed with KCl (2.75 g) and LiBr (2.25 g) and then transferred to a covered crucible and calcined at 550 °C for 4 h (heating rate of 5 °C min-1) in air atmosphere. -1 ), after natural cooling, the mixture was fully washed with deionized water to remove the mixed salt, the solid residue was separated, and the homogeneous carbon-doped carbon nitride photocatalyst THCN was obtained by drying. 0.05 -500.
[0075] Example 7
[0076] THCN 0.02 -400 Photocatalyst preparation:
[0077] (1) 10 g of melamine and 0.02 g of 2,4,6-triaminopyrimidine powder were placed in a mortar and mixed thoroughly. The mixture was then transferred to a crucible and calcined at 400 °C for 4 h (heating rate was 5 °C min -1 ) to obtain a carbon-doped triazine / heptazine mixture.
[0078] (2) The mixture obtained in step (1) was ultrasonically dispersed in water at 60° C., then slowly cooled to room temperature and shaken for 24 h, the water was removed by rotary evaporation (the heating temperature was controlled at 60° C.), and then placed in a vacuum oven at 40° C. for further drying to obtain a solid supramolecular precursor.
[0079] (3) The supramolecular precursor (1 g) obtained in step (2) was uniformly mixed with KCl (2.75 g) and LiBr (2.25 g) and then transferred to a covered crucible and calcined at 550 °C for 4 h (heating rate of 5 °C min-1) in air atmosphere. -1 ), after natural cooling, the mixture was fully washed with deionized water to remove the mixed salt, the solid residue was separated, and the homogeneous carbon-doped carbon nitride photocatalyst THCN was obtained by drying. 0.02 -400.
[0080] Example 8
[0081] THCN 0.1 -400 Photocatalyst preparation:
[0082] (1) 10 g of melamine and 0.1 g of 2,4,6-triaminopyrimidine powder were placed in a mortar and mixed thoroughly. The mixture was then transferred to a crucible and calcined at 400 °C for 4 h (heating rate was 5 °C min -1 ) to obtain a carbon-doped triazine / heptazine mixture.
[0083] (2) The mixture obtained in step (1) was ultrasonically dispersed in water at 60° C., then slowly cooled to room temperature and shaken for 24 h, the water was removed by rotary evaporation (the heating temperature was controlled at 60° C.), and then placed in a vacuum oven at 40° C. for further drying to obtain a solid supramolecular precursor.
[0084] (3) The supramolecular precursor (1 g) obtained in step (2) was uniformly mixed with KCl (2.75 g) and LiBr (2.25 g) and then transferred to a covered crucible and calcined at 550 °C for 4 h (heating rate of 5 °C min-1) in air atmosphere. -1 ), after natural cooling, the mixture was fully washed with deionized water to remove the mixed salt, the solid residue was separated, and the homogeneous carbon-doped carbon nitride photocatalyst THCN was obtained by drying. 0.1 -400.
[0085] Example 9
[0086] THCN 0.5 -400 Photocatalyst preparation:
[0087] (1) 10 g of melamine and 0.5 g of 2,4,6-triaminopyrimidine powder were placed in a mortar and mixed thoroughly. The mixture was then transferred to a crucible and calcined at 400 °C for 4 h (heating rate was 5 °C min -1 ) to obtain a carbon-doped triazine / heptazine mixture.
[0088] (2) The mixture obtained in step (1) was ultrasonically dispersed in water at 60° C., then slowly cooled to room temperature and shaken for 24 h, the water was removed by rotary evaporation (the heating temperature was controlled at 60° C.), and then placed in a vacuum oven at 40° C. for further drying to obtain a solid supramolecular precursor.
[0089] (3) The supramolecular precursor (1 g) obtained in step (2) was uniformly mixed with KCl (2.75 g) and LiBr (2.25 g) and then transferred to a covered crucible and calcined at 550 °C for 4 h (heating rate of 5 °C min-1) in air atmosphere. -1 ), after natural cooling, the mixture was fully washed with deionized water to remove the mixed salt, the solid residue was separated, and the homogeneous carbon-doped carbon nitride photocatalyst THCN was obtained by drying. 0.5 -400.
[0090] Comparative Example 1
[0091] Preparation of Bulk Carbon Nitride (Bulk-CN) Photocatalyst:
[0092] 1 g of melamine powder was directly placed in a covered crucible and calcined at 550 °C for 4 h (heating rate was 5 °C min -1 ), after natural cooling, fully grind to obtain bulk carbon nitride Bulk-CN.
[0093] Figure 2The XRD patterns of the catalysts prepared in Examples 1 to 6 and Comparative Example 1. As the pretreatment temperature increases, the peaks at 2θ=8.1° and 28.0° gradually increase, corresponding to the (100) and (002) crystal planes of the heptazine structure carbon nitride. The XRD diffraction peak positions of Bulk-CN with a heptazine structure are slightly deviated, due to the different preparation methods, and the Bulk-CN obtained by direct calcination of melamine has serious stacking of flakes, and the (002) crystal plane diffraction intensity is large. The diffraction peaks at 2θ=12.0, 21.0, 24.3, 26.6, 29.3 and 32.2° weaken to disappear. This group of diffraction peaks corresponds to triazine structure carbon nitride, and the diffraction peaks disappear as the pretreatment temperature increases, indicating that the triazine structure in the precursor gradually decreases. After the pretreatment temperature is above 450°C, there is almost only a heptazine structure in the precursor, and the prepared carbon nitride is a heptazine structure carbon nitride. When the pretreatment temperature is 400℃, the XRD diffraction peaks show the coexistence of heptazine carbon nitride and triazine carbon nitride, which confirms that the prepared carbon nitride contains triazine / heptazine homojunction at this pretreatment temperature. When the pretreatment temperature is lower than 350℃, the prepared carbon nitride is mainly triazine structure.
[0094] Figure 3 The UV-visible diffuse reflectance spectra of Example 3 and Comparative Example 1 are shown in Table 1. Compared with Bulk-CN, THCN in Example 3 0.05 -400 absorption sideband is red-shifted, with a wider light absorption range.
[0095] Figure 4 The Tauc plots of Example 3 and Comparative Example 1 are shown. 0.05 The band gap of -400 is 2.75eV, which is smaller than that of Bulk-CN (2.82eV), which is more conducive to light absorption and thus obtains better catalytic activity.
[0096] Comparative Example 2
[0097] Preparation of THCN-300 photocatalyst:
[0098] (1) 10 g of melamine powder was calcined at 300 °C for 4 h (heating rate was 5 °C min -1 ), to obtain a triazine / heptazine mixture.
[0099] (2) The mixture obtained in step (1) was ultrasonically dispersed in water at 60° C., then slowly cooled to room temperature and shaken for 24 h, the water was removed by rotary evaporation (the heating temperature was controlled at 60° C.), and then placed in a vacuum oven at 40° C. for further drying to obtain a solid supramolecular precursor.
[0100] (3) The supramolecular precursor (1 g) obtained in step (2) was uniformly mixed with KCl (2.75 g) and LiBr (2.25 g) and then transferred to a covered crucible and calcined at 550 °C for 4 h (heating rate of 5 °C min-1) in air atmosphere. -1 ), after natural cooling, fully washing with deionized water to remove mixed salts, separating solid residues, and drying to obtain a homogeneously distributed carbon-doped carbon nitride photocatalyst THCN-300.
[0101] Comparative Example 3
[0102] Preparation of THCN-400 photocatalyst:
[0103] (1) 10 g of melamine powder was calcined at 400 °C for 4 h (heating rate was 5 °C min -1 ), to obtain a triazine / heptazine mixture.
[0104] (2) The mixture obtained in step (1) was ultrasonically dispersed in water at 60° C., then slowly cooled to room temperature and shaken for 24 h, the water was removed by rotary evaporation (the heating temperature was controlled at 60° C.), and then placed in a vacuum oven at 40° C. for further drying to obtain a solid supramolecular precursor.
[0105] (3) The supramolecular precursor (1 g) obtained in step (2) was uniformly mixed with KCl (2.75 g) and LiBr (2.25 g) and then transferred to a covered crucible and calcined at 550 °C for 4 h (heating rate of 5 °C min-1) in air atmosphere. -1 ), after natural cooling, the mixture was fully washed with deionized water to remove the mixed salt, the solid residue was separated, and the mixture was dried to obtain the carbon-doped carbon nitride photocatalyst THCN-400 with homogeneous junction and uniform distribution.
[0106] Comparative Example 4
[0107] Preparation of THCN-500 photocatalyst:
[0108] (1) 10 g of melamine powder was calcined at 500 °C for 4 h (heating rate was 5 °C min -1 ), to obtain a triazine / heptazine mixture.
[0109] (2) The mixture obtained in step (1) was ultrasonically dispersed in water at 60° C., then slowly cooled to room temperature and shaken for 24 h, the water was removed by rotary evaporation (the heating temperature was controlled at 60° C.), and then placed in a vacuum oven at 40° C. for further drying to obtain a solid supramolecular precursor.
[0110] (3) The supramolecular precursor (1 g) obtained in step (2) was uniformly mixed with KCl (2.75 g) and LiBr (2.25 g) and then transferred to a covered crucible and calcined at 550 °C for 4 h (heating rate of 5 °C min-1) in air atmosphere. -1 ), after natural cooling, fully washing with deionized water to remove mixed salts, separating solid residues, and drying to obtain a homogeneously distributed carbon-doped carbon nitride photocatalyst THCN-500.
[0111] Test Case
[0112] The carbon nitride photocatalysts obtained in the above embodiments and control examples were used as catalysts to carry out photocatalytic benzyl alcohol oxidation reaction. The specific reaction method is as follows:
[0113] Take 15 mg of each carbon nitride photocatalyst powder obtained in the above examples and control examples, and uniformly disperse them in 8 mL of acetonitrile by ultrasonication. Add 0.2 mmol of benzyl alcohol, transfer the reaction mixture to a quartz reaction tube, replace the residual air in the reaction tube with oxygen, and connect the reaction tube to an oxygen balloon for reaction. The light source is a Xe lamp, the reaction temperature is controlled at 60°C, and the reaction time is 4 hours; the product is detected by gas chromatography, and the conversion rate and selectivity are calculated by normalization method.
[0114] Table 1 Comparison of the oxidative performance of various photocatalysts
[0115]
[0116]
[0117] (Conv. 苯甲醇 (%) indicates conversion rate, Sel. 苯甲醛 (%) is the proportion of benzaldehyde in the product, Sel. 苯甲酸 (%) is the proportion of benzoic acid in the product)
[0118] Table 1 is a comparison of the photocatalytic oxidation performance of benzyl alcohol under the conditions described in the test example. Bulk carbon nitride (Comparative Example 1) has the lowest conversion rate and the worst oxidation performance. The reason is that the carbon nitride photocatalyst prepared by direct thermal polymerization of melamine usually has serious flake stacking, a small comparative area, and serious photogenerated carrier recombination. For the carbon-doped carbon nitride photocatalyst with homojunction structure (Examples 1 to 6), as the pretreatment temperature increases, the photocatalyst performance first increases and then decreases. Example 3 shows the best catalytic activity, and the product is mainly benzaldehyde at a reaction time of 4h. In comparison, the performance of the catalyst without carbon doping is insufficient (Comparative Examples 2 to 4). If the carbon doping amount is too little or too much, the catalyst performance will also decrease (Examples 7 to 9). The reason is that carbon doping can promote the separation of photogenerated electron-hole pairs. If the doping amount is small, the number of separation centers is small, and the carrier separation effect is insufficient; if the doping amount is too much, it will destroy the carbonized skeleton structure, allowing the photocatalyst to change from a semiconductor to a conductor, which is not conducive to light absorption and photogenerated carrier separation. In summary, thanks to the molecular rearrangement under supramolecular self-assembly, the precursors can be evenly mixed at the microscopic scale, so that the triazine / heptazine homojunction structure can be evenly distributed. Combined with carbon doping, the photocatalytic oxidation performance of benzyl alcohol by carbon nitride photocatalyst can be effectively improved.
[0119] Table 2 THCN 0.05 -400 catalyst selectivity test results under different conditions
[0120]
[0121]
[0122] (“+” in the table means optional; “-” means not optional)
[0123] Table 2 THCN 0.05 -400 catalyst photocatalytic oxidation results of benzyl alcohol under different conditions. Comparing No. 1 and No. 2, it can be seen that the reaction must be carried out under light conditions. Comparing No. 3 and No. 4, due to superoxide free radicals, photogenerated holes are the key factors affecting the reaction. Under anaerobic conditions, photogenerated holes can only oxidize benzyl alcohol to benzaldehyde, and due to the existence of some photogenerated electron-hole pair recombination phenomena, the conversion rate is not high; under aerobic conditions, superoxide free radicals are generated in the system, and if the reaction time is long enough, benzaldehyde can be further completely oxidized to benzoic acid. Lowering the reaction temperature, the catalyst effect decreases slightly (No. 5). Comparing No. 6 and No. 7, when K is added 2 S 2 O 8 As an electron capture agent, the complete conversion of benzaldehyde or benzoic acid can be achieved by controlling the reaction atmosphere.
[0124] Figure 5THCN prepared in Example 3 0.05 -400 catalyst photocatalytic benzyl alcohol oxidation cycle performance diagram, each cycle time is 4h. After 5 cycles, the catalytic effect decreased slightly, and the product was mainly benzaldehyde.
[0125] Figure 6 THCN prepared in Example 3 0.05 -400 catalyst photocatalytic benzyl alcohol oxidation cycle performance diagram, each cycle time is 12h. After 5 cycles, the conversion rate of benzyl alcohol did not decrease significantly, and the product was almost entirely benzoic acid. However, in the last two cycles, a small amount of benzaldehyde appeared in the product. The test results under both conditions showed that THCN 0.05 -400 catalyst has excellent cycle stability.
Claims
1. A method for preparing a triazine / heptazine homojunction structure carbon-doped carbon nitride photocatalyst, characterized in that: The specific steps are: (1) placing a mixed powder of melamine and 2,4,6-triaminopyrimidine in air, heating it to 300° C. to 500° C., and calcining it for 2 to 6 hours to form a mixture of carbon-doped melamine and its oligomers; (2) placing the mixture obtained in step (1) in water at 60 to 70° C., ultrasonically dispersing the mixture, then slowly cooling the mixture to room temperature and oscillating the mixture for 12 to 36 hours, removing water by rotary evaporation, and drying the mixture to obtain a solid supramolecular precursor; (3) After the solid supramolecular precursor obtained in step (2) is fully mixed with the molten salt, it is calcined at 500° C. to 600° C. for 2 to 6 hours, cooled and fully washed with deionized water to remove the mixed salt, separate the solid residue, and dry to obtain a triazine / heptazine homojunction structure carbon-doped carbon nitride photocatalyst THCN. x -t.
2. A method for preparing the triazine / heptazine homojunction carbon-doped carbon nitride photocatalyst according to claim 1, characterized in that: In the step (1), the heating rate is 5°C min -1 .
3. The method for preparing the triazine / heptazine homojunction carbon-doped carbon nitride photocatalyst according to claim 1, characterized in that: In the step (1), the mass ratio of melamine to 2,4,6-triaminopyrimidine is 10:0.02-0.
5.
4. The method for preparing the triazine / heptazine homojunction carbon-doped carbon nitride photocatalyst according to claim 3, characterized in that: In the step (1), the mass ratio of melamine to 2,4,6-triaminopyrimidine is 10:0.
05.
5. The method for preparing the triazine / heptazine homojunction carbon-doped carbon nitride photocatalyst according to claim 1, characterized in that: In the step (2), the mixture is ground into fine powder before being ultrasonically dispersed in water, and the concentration of the mixture in water is 25 g / L.
6. The method for preparing the triazine / heptazine homojunction carbon-doped carbon nitride photocatalyst according to claim 2, characterized in that: In the step (3), the molten salt is a composition of KCl and LiBr, and the mass ratio of the solid supramolecular precursor, KCl and LiBr is 1:2.75:2.
25.
7. A triazine / heptazine homojunction carbon-doped carbon nitride photocatalyst, characterized in that: The invention is prepared by the method according to any one of claims 1 to 6.
8. Use of the triazine / heptazine homojunction structure carbon-doped carbon nitride photocatalyst as claimed in claim 7 in photocatalytic selective oxidation.
9. Use of the triazine / heptazine homojunction structure carbon-doped carbon nitride photocatalyst in photocatalytic selective oxidation as claimed in claim 8, characterized in that: Benzyl alcohol is used as a reaction substrate, acetonitrile is used as a reaction medium, a triazine / heptazine homojunction carbon-doped carbon nitride photocatalyst is used as a photocatalyst, a xenon lamp is used as a light source, an oxidant is added, a reaction system is formed, and benzaldehyde and / or benzoic acid are prepared.
10. Use of the triazine / heptazine homojunction carbon-doped carbon nitride photocatalyst in photocatalytic selective oxidation as claimed in claim 9, characterized in that: The reaction conditions are: the reaction temperature is controlled at 60°C, the reaction time is 1 to 12 hours, and the concentration of benzyl alcohol in the reaction system is 50 mmol·L -1 , the carbon nitride photocatalyst concentration is 4 g·L -1 , the oxidant is oxygen.
Citation Information
Patent Citations
High-efficiency carbon self-doped graphite phase carbon nitride visible light photocatalyst, and preparation method and application thereof
CN106902859A
Molten salt preparation method and application of copolymerization modified carbon nitride / zinc oxide composite visible light responsive photocatalyst
CN109012726A
Method for preparing triazine / heptaazine allotropic heterojunction carbon nitride photocatalyst
CN109590006A
Carbon-doped supramolecular polymerized carbon nitride visible-light-driven photocatalyst and application thereof
CN114225957A
Preparation method and application of carbon nitride semiconductor photocatalyst containing heptazine / triazine homojunction structure
CN117101701A
Cited By
Triazine-heptazine homojunction carbon nitride as well as preparation method and application thereof
CN120394061A
Carbon-doped carbon nitride nanotube, preparation method thereof and application of carbon-doped carbon nitride nanotube in photocatalytic reaction
CN120885254A
Photocatalyst capable of generating superoxide radicals with high selectivity as well as preparation method and application of photocatalyst
CN121372495A